The Ochodaeidae of Argentina (Coleoptera, Scarabaeoidea) - Paulsen, M. J. (2012)
The Ochodaeidae (Coleoptera: Scarabaeoidea) of Argentina are revised. Previously, two species of Ochodaeinae were known from the country, both in the genus Parochodaeus Nikolajev: P. campsognathus (Arrow) and P. cornutus (Ohaus). An additional 7 species of Parochodaeus from Argentina are described here as new. In addition, Gauchodaeus patagonicus, new genus and new species in the subfamily Chaetocanthinae, is described. "is is the #rst record of the subfamily Chaetocanthinae in South America. Redescriptions, diagnoses, and maps are provided for each species. We also provide a key to genera and a key to species of Parochodaeus of Argentina. With this work, the number of ochodaeid species known from Argentina is increased from 2 to 10.